EFL Students’ Anxiety in Responding to Teachers’ Questions - Amalia, Nurul Rezky; Jabu, Baso; Sakkir, Geminastiti (Journal of Excellence in English Language Education, 2026)
This study investigates EFL students’ anxiety in responding to teachers’ questions, focusing on the underlying contributing factors and the strategies that effectively reduce this anxiety. Using a qualitative case study approach, the research was conducted at SMPN 2 Barombong with eighth-grade students as the participants. Data were collected through classroom observations and semi-structured interviews. The findings reveal that fear of making mistakes, lack of confidence, and limited vocabulary are the main factors contributing to students’ anxiety. These factors often cause students to hesitate, remain silent, or avoid responding altogether during classroom interactions. The study also identifies several effective strategies to minimize anxiety, including building positive teacher-student relationships, creating fun learning activities, using humor and positive thinking, and providing rewards. These strategies help build a supportive classroom environment that fosters students’ confidence and reduces the fear of negative evaluation. This research offers significant insights for teachers and future researchers in understanding and addressing EFL students' speaking anxiety.